ECONOMIC ASPECTS OF IMPROVING THE EFFICIENCY OF RAW MATERIAL SUPPLIES IN COTTON-TEXTILE COMPLEXES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the economic aspects of increasing the efficiency of raw material supply in the cotton-textile clusters of Uzbekistan. The trends in the development of cotton-textile clusters in the country, production volumes, labor productivity, export indicators, as well as the dynamics of raw materials and material costs are analyzed.
Keywords: cotton and textile cluster, supply of raw materials, labor productivity, export potential, production efficiency, logistics, value added, resource use.